(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to investigate and analyze the implementation of transparency in public services in making driving licenses at the Makassar City Police. This research uses qualitative research methods with case study analysis to evaluate the implementation of transparency in public services regarding public service procedures, details of service costs, and public service information in the Driving License Making study. The research results show that the implementation of transparency in public services (study of making driving licenses) at Makassar City Police is based on three research indicators, namely 1. Public service procedures which include openness on social networks by creating content regarding SOPs for making driving licenses. 2. Details of service costs are observed to be cheap and do not change. 3. Service information is transparent because all applicable SOPs are followed and services are via the web or application. However, there are still inhibiting factors in the driving license making service, namely that it has not been implemented optimally because the service depends on the system server.